2013
DOI: 10.1186/1687-1812-2013-168
|View full text |Cite
|
Sign up to set email alerts
|

Fixed points of some new contractions on intuitionistic fuzzy metric spaces

Abstract: We introduce some new contractions on intuitionistic fuzzy metric spaces, and give fixed point results for these classes of contractions. A stability result is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Wardowski [29] familiarized a concept of mapping on soft sets and determined its fixed point. A vast amount of mathematical activity has been carried out to obtain fixed points of various mappings, as studied by many authors [8,9,26,[28][29][30][31]. In the present study, we obtain some results on fixed points of fns-mappings.…”
Section: Introductionmentioning
confidence: 70%
“…Wardowski [29] familiarized a concept of mapping on soft sets and determined its fixed point. A vast amount of mathematical activity has been carried out to obtain fixed points of various mappings, as studied by many authors [8,9,26,[28][29][30][31]. In the present study, we obtain some results on fixed points of fns-mappings.…”
Section: Introductionmentioning
confidence: 70%
“…Corollary 18 (Theorem 2.1 in [19]). Let ( , , , * , ⬦) be a complete triangular intuitionistic fuzzy metric space and let : → be a continuous mapping satisfying the contractive condition…”
Section: From Parametric Metric To Triangular Intuitionistic Fuzzy Mementioning
confidence: 98%
“…By taking P( , , ) = 1/ ( , , ) − 1 and ℓ( ) = 1/ in Theorem 16, we deduce the following result. Corollary 20 (Theorem 2.2 in[19]). Let ( , , , * , ⬦) be a complete triangular intuitionistic fuzzy metric space and let : → be a continuous mapping satisfying the contractive condition…”
mentioning
confidence: 97%
“…He showed that for each intuitionistic fuzzy metric space (X, M, N, * , ♦), the topology generated by the intuitionistic fuzzy metric (M, N ) coincides with the topology generated by the fuzzy metric M . For more details on intuitionistic fuzzy metric space and related results we refer the reader to [2,7,9,13,19,[21][22][23]27]. In 2006, Saadati and Park introduced the notion of intuitionistic fuzzy normed space [25].…”
Section: Introductionmentioning
confidence: 99%
“…Let X be vector space, * be a continuous t-norm and M be a fuzzy set on X ×(0, 1) satisfying the following conditions: for all x, y ∈ X, s, t > 0, Proof. It is sufficient to check the conditions (8)- (13). From the relation…”
mentioning
confidence: 99%